PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT POS INDONESIA CABANG CIPUTAT TANGERANG SELATAN - Indah Pramesthi, Mutia; Sutrisno (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of work motivation and work discipline on employee performance at PT Pos Indonesia Ciputat Branch. This research uses quantitative methods with data collection techniques through distributing questionnaires and library/literature data. The population in this study were 139 employees. The sample used was 59 employees using the Slovin technique. The data analysis used is validity test analysis, reliability test, classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, determination coefficient test and hypothesis testing with the help of SPSS 26 software. The results showed that partially work motivation has a significant effect on employee performance, it can be seen that the correlation value is 0.598  where the value has a strong relationship level. The coefficient of determination is 35.8%, while the remaining 64.2% is influenced by other factors. And the t test results obtained a tcount value of 5.378> t table 1.673 and a significant 0.003 <0.05. discipline has a significant effect on employee performance, it can be seen that the correlation value is 0.772 where the value has a strong level of relationship. The determination value is 59.7%, while the remaining 40.3% is influenced by other factors. The t test results obtained a tcount value of 6.176> t table 1.673 and a significant 0.000 <0.05. Simultaneously the effect of work motivation and work discipline on employee performance has a positive and significant effect, this can be proven by the regression equation Y = 9.375 + 0, 279  X1 + 0.516 X2, the correlation value of 0.801 means that the independent variable with the dependent variable has a very strong level of relationship, the coefficient of determination is 63.6%, while the remaining 36.4% is influenced by other factors. Similarly, the results of the F test show that fhitung>ftabel is 49.368,> 3.16 and the significance is 0.000 <0.05 which means that work motivation and work discipline have a significant effect on employee performance at PT Pos Indonesia Ciputat Branch.